Lymphoplasmapheresis versus plasma exchange in severe myasthenia gravis: a retrospective cohort study - Duan, Weiwei; Jiang, Fei; Cai, Haobing; Li, Bijuan; Ouyang, Song; Yin, Weifan; Zeng, Qiuming; Yang, Huan (Frontiers in Neurology, 2023)
Background Lymphoplasmapheresis (LPE) is a new therapy developed on the basis of traditional plasma exchange (PE) in combination with leukapheresis. Currently, it remains unclear whether PE and LPE show differences in efficacy for severe MG. Methods A retrospective analysis was conducted on 198 MG patients, 75 in the PE group and 123 in the LPE group, and the patients’ Myasthenia Gravis Foundation of America (MGFA) Clinical Classification was Class IV. The treatment outcome was the change in Quantitative Myasthenia Gravis Score (QMGS) from baseline to the end of treatment. Propensity score matching (PSM) was applied for the balance of confounders between the two groups. Results In this study cohort, the safety profile of LPE and PE was good and no serious adverse events were observed. Based on PSM, 62 patients treated with LPE and 62 patients treated with PE were entered into a comparative efficacy analysis. In the PE group, patients underwent a total of 232 replacements, with a mean of 3.74. PE significantly improved the patients’ QMGS performance, with the mean QMGS decreasing from 22.98 ± 4.03 points at baseline to 18.34 ± 5.03 points after treatment, a decrease of 4.68 ± 4.04 points (p < 0.001). A decrease of ≥3 points in QMGS was considered a significant improvement, with a treatment response rate of 67.7% in the PE group. In the LPE group, patients received a total of 117 replacements, with a mean of 1.89. The patients’ mean QMGS was 23.19 ± 4.11 points at baseline and was 16.94 ± 5.78 points after treatment, a decrease of 6.26 ± 4.39 points (p < 0.001). The improvement in QMGS was more significant in patients treated with LPE compared to the PE group (p = 0.039). The treatment response rate in the LPE group was 79%, which was not significantly different compared to the PE group (p = 0.16). The LEP group had a shorter mean length of stay compared to the PE group (10.86 ± 3.96 vs. 12.14 ± 4.14 days), but the difference was not statistically significant (p = 0.13). During the 2-month follow-up period, LPE may be associated with better functional outcomes for patients, with lower QMG score and relapse rate. LPE and PE were both effective in reducing the levels of inflammatory cytokines (TNF-α, IL-1β, and IL-6) and AChR-Ab. Compared to PE, LPE was superior in the reduction of AChR-Ab titer. Conclusion In severe MG, LPE may be a more preferred treatment option than PE. It achieves treatment outcomes that are not inferior to or even better than PE with fewer replacements. This study provides further evidence to support the application of LPE as a new treatment option for MG.